Metaverse : Media Pembelajaran di Era Society 5.0 untuk Meningkatkan Kualitas Pendidikan Indonesia - Dwi Maulan Pangestu; Azizu Rahmi (Universitas Negeri Padang, 2022)
Metaverse is a three-dimensional virtual technology renewal or innovation that can be used as a learning medium in the era of society 5.0 and can improve the quality of education in Indonesia. This research study discusses the metaverse that can be used as a learning medium in the era of society 5.0 to improve the quality of Indonesian education in the future. The research method used is a literature study by collecting library data from various scientific journal sources relevant to the use of the metaverse from 2020-2022. The results show that the metaverse has developed rapidly from 2020 to 2002, considering that the metaverse is an interconnected social network, an immersive network environment within a platform with many persistent users. The forms of metaverse that have been implemented such as augmented reality and virtual reality, which are present to answer the problems during the pandemic and also the needs of the era of society 5.0, in an effort to improve the quality of education in Indonesia by utilizing augmented reality and virtual reality in skills learning processes. very helpful at full term and in order to realize the quality of education in the era of society 5.0. The use of metaverse in Indonesia is generally widely used at the high school and university level in their learning. The use of metaverse with management that is in accordance with current needs, can be one of the factors supporting the success of applying metaverse to improve the quality of education in Indonesia in the next 10 to 15 years.